Theoretical Studies on Electronic Transport Properties of 2,5-Dimercapto-Pyridazin Molecular Junctions: Influence of $CO$ and $H_2O$ Molecules (Journal of Atomic and Molecular Sciences, 2015)
Based on first-principles calculations, the electrode force acted on 2,5-dimercapto-pyridazin molecular device is studied. The pressing effects of $CO$ and $H_2O$ molecules on the 2,5-dimercapto-pyridazin molecular junctions are also studied atB3LYP level to simulate the effects of little ambient molecules on the functional molecularjunctions. The electronic transport properties of 2,5-dimercapto-pyridazin molecularjunction with the pressing of $CO$ and $H_2O$ molecules are studied by employingelastic scattering Green's function method. The numerical results show that the 2,5-dimercapto-pyridazin can be squeezed out of the electrode gap when the electrodedistance is compressed to 1.02 nm. It needs about 1.5 nN stretching force to breakdown the 2,5-dimercapto-pyridazin molecular junction, which agrees with the experimentprobes very well. The 2,5-dimercapto-pyridazin molecule is bent by the pressingof $CO$ or $H_2O$ molecule, and is pushed to the edge of Au (111) triangles with the terminalS atoms first to the bridge and then to the top positions of Au (111) triangles,until at last one terminal S atom is pushed out of Au (111) triangle. The pressingof $CO$ and $H_2O$ molecules to the molecular junctions will enhance the couplings betweenmolecule and electrodes, which further enhances nonresonant transmission ofthe molecular junctions.
Keywords: molecular device; 2; 5-dimercapto-pyridazin molecule; electronic transport properties; effect of small ambient molecule.